REDES DE COOPERAÇÃO, DA FORMAÇÃO AOS RESULTADOS: UM ESTUDO DAS ORGANIZAÇÕES DO PROGRAMA EMPREENDER - CHRIST, EDUARDO (2017)
This research aims at understanding the reasons why companies work with inter-organizational relationships, comprehending what leads companies to get united with others, having as an objective to identify the formation and maintenance factors, as well as the results achieved by microenterprises in two inter-organizational networks belonging to the program “Empreender” in the region of Guarapuava. Therefore, it was aimed through literature to list the determining factors to the development of this relation, being listed as determinants the comprehension of the factors related to the formation and maintenance (named as facilitating factors and difficult factors during this work) and the results from these companies. To understand the theme it was chosen as working field the program “Empreender” in the city of Guarapuava, in the state of Paraná. For this purpose, two sectorial centers were chosen for this research applicability: 1) Communication center; 2) information technology center. At first, the motivating factors in the formation of the relation were investigated, afterward the facilitating factors and difficult factors and eventually the results. To reach the research objectives, the strategy of case study and qualitative methods were used. The results obtained after the application of the research pointed out the main motivating factors in the relation as i) efficiency, looking for partnerships and information that allow development of the business management; ii) reciprocity was important for the formation of the center, the reliance and closeness from some entrepreneurs were a motivating factor; iii) legitimacy of companies for cooperating with others in order to have a better appreciation from the market of great prestige and safety were also one of the factors pointed as motiving by the research. Regarding the facilitating and difficult factors, it was verified that the main difficult factors were related to the lack of organization and planning of the meetings and the absence of some entrepreneurs during them. As facilitating factors there were: common goals, reliance among companies, facilitating team and democratic environment. Regarding the results obtained through the relationships, it was noticed an increase in the cooperation levels of the organizations, better relation to the competitors and the key result according to the research is related to knowledge gained through the participation in the center. It can be considered that organizations had as initial goal improvement of their relations with competitors, after the participation their goals were directed to the management development, and these are the reasons why entrepreneurs are still participating. The practical contributions pointed out by this study were: setting of the goals from each center and tracking of the results; facilitating the access to the centers, inviting more companies to join; performing more training actions to entrepreneurs; executing a management diagnostic in each center; bringing up results directly to the organization; sharing management tools; creating common indicators to monitor the results; trying to emphasize the increment of the center for the community in order to have a better program and participants.